Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có : z = \(\frac{m}{n}\)= \(\frac{\frac{a+c}{2}}{\frac{b+d}{2}}=\frac{a+c}{b+d}=\frac{2m}{2n}\)
Nếu x < y thì \(\frac{a}{b}< \frac{a+c}{b+d}< \frac{c}{d}\)\(\Rightarrow\frac{a}{b}< \frac{2m}{2n}< \frac{c}{d}\)
\(\Rightarrow\frac{a}{b}< \frac{m}{n}< \frac{c}{d}\)\(\Rightarrow x< z< y\)
Nếu x > y thì : \(\frac{a}{b}>\frac{a+c}{b+d}>\frac{c}{d}\)\(\Rightarrow\frac{a}{b}>\frac{2m}{2n}>\frac{c}{d}\)
\(\Rightarrow\frac{a}{b}>\frac{m}{n}>\frac{c}{d}\)\(\Rightarrow x>z>y\)
Vậy ...
Ta có: \(\frac{a}{b}\)=\(\frac{c}{d}\)
+ \(\frac{a}{b}\)=\(\frac{a}{b}\).\(\frac{a}{b}\)=\(\frac{a^2}{b^2}\) (1)
+ \(\frac{a}{b}\)=\(\frac{c}{d}\)=\(\frac{ac}{bd}\) (2)
Từ (1); (2) => \(\frac{a}{b}\)=\(\frac{c}{d}\)=>\(\frac{a^2}{b^2}\)=\(\frac{ac}{bd}\)
Ta có \(\frac{a}{b}=\frac{c}{d}\Rightarrow\left(\frac{a}{b}\right)^2=\frac{a^2}{b^2}=\left(\frac{c}{d}\right)^2=\frac{a.c}{b.d}\left(ĐPCM\right)\)
b) x-y=a/b-c/d=ad/bd-bc/bd suy ra x-y=ad-bc phan bd
cau a hinh nhu sai de